Eldorado, or, Adventures in the path of empire: comprising a voyage to California, via Panama; life in San Francisco and Monterey; pictures of the gold region, and experiences of Mexican travel. - Taylor, Bayard, 1825-1878.; King, T. Butler (Thomas Butler), 1800-1864. (New York, G.P. Putnam; London, R. Bentley, 1850)
Bayard Taylor (1825-1878) was already a well-established writer when he traveled to California as special correspondent for the New York Tribune in the summer of 1849. On his return to New York, Taylor established himself not only as one of America's great travel writers but as a true man of letters, producing distinguished novels and poems as well as nonfiction for the next quarter century. Eldorado (1850) consists of Taylor's rewritten dispatches to his paper. Volume 2 tells of the 1849 elections, horseback tours of the Sierras, gold camps on the Mokelumne River, analysis of the 1849 overland emigration, San Francisco social and cultural life, and a return to the East with stops in Guadalajara, Mazatlàn, Mexico City, Popcateptel, and Vera Cruz. Thomas Butler King's official report on California, 22 March 1850, is printed as an appendix.
Appendix: Report of Hon. T. Butler King. v. 2, p. 199-247.
Also available in digital form on the Library of Congress Web site.
Keywords: California -- Gold discoveries; California -- Description and travel; Voyages to the Pacific coast; Mexico -- Description and travel; Ethnic groups -- California